1996
DOI: 10.1111/j.1151-2916.1996.tb08986.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Crystal Phases of Praseodymium Oxides in Zinc Oxide Varistor Ceramics

Abstract: The effect of sintering temperature on the microstructure and crystal phases of the intergranular praseodymium oxides in ZnO varistor ceramics was investigated using transmission electron microscopy and high‐resolution electron microscopy. The ZnO grains were three‐dimensionally separated from the intergranular praseodymium oxides. On the basis of microdiffraction analyses of the intergranular layer, the phase transformation from fcc‐Pr6O11 into hcp‐Pr2O3 was found when the sintering temperature increased from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…Zn-Pr-based varistors have been studied to further enhance varistor properties and the stability against various stresses, compared to Zn-Bi-based varistors. Most investigations on Zn-Pr-based varistors have been reported on the microstructure and electrical properties in terms of additives and sintering processing [6][7][8][9][10][11][12][13][14][15][16]. In particular, Nahm et al reported the effect of rare earth oxides and lanthanum oxide on electrical properties and its stability against DC accelerated degradation stress [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Zn-Pr-based varistors have been studied to further enhance varistor properties and the stability against various stresses, compared to Zn-Bi-based varistors. Most investigations on Zn-Pr-based varistors have been reported on the microstructure and electrical properties in terms of additives and sintering processing [6][7][8][9][10][11][12][13][14][15][16]. In particular, Nahm et al reported the effect of rare earth oxides and lanthanum oxide on electrical properties and its stability against DC accelerated degradation stress [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, it also deteriorates the surge absorption capabilities due to a decrease of effective grain boundary area. To overcome these problems, Zn-Pr-based varistors have been actively studied [6][7][8]. Zn-Pr-based varistors have been studied to further enhance varistor properties and the stability against various stresses, compared to Zn-Bi-based varistors.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations for ZnO-Pr 6 O 11 -based varistor ceramics have been reported on the microstructure and electrical properties in terms of additives, and sintering temperature and time [4][5][6][7][8][9][10][11][12][13][14][15]. In particular, the effect of rare earth oxides (Pr 6 O 11 , Er 2 O 3 , Dy 2 O 3 , Tb 4 O 7 , etc) on electrical properties and its stability [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…ZnO-Pr 6 O 11 -based varistor ceramics have been studied to further enhance the varistor properties [5][6][7][8][9][10][11]. Nahm et al reported that Zn-Pr-Co-Cr (ZPCC)-Rare earth oxide (R = Er, Y, Dy, etc.…”
Section: Introductionmentioning
confidence: 99%